Contact line motion on nanorough surfaces: A thermally activated process - Ramiasa, M.; Ralston, J.; Fetzer, R.; Sedev, Rossen; Fopp-Spori, D.; Morhard, C.; Pacholski, C.; Spatz, J. (American Chemical Society, 2013)
The motion of a solid-liquid-liquid contact line over nanorough surfaces is investigated. The surface nanodefects are varied in size, density, and shape. The dynamics of the three-phase contact line on all nanorough substrates studied is thermally activated. However, unlike the motion of a liquid-vapor interface over smooth surfaces, this thermally activated process is not adequately described by the molecular kinetic theory. The molecular parameters extracted from the experiments suggest that on the nanorough surfaces, the motion of the contact line is unlikely to simply consist of molecular adsorption-desorption steps. Thermally activated pinning-depinning events on the surface nanodefects are also important. We investigate the effect of surface nanotopography on the relative importance of these two mechanisms in governing contact line motion. Using a derivation for the hysteresis energy based on Joanny and de Gennes's model, we evaluate the effect of nanotopographical features on the wetting activation free energy and contact line friction. Our results suggest that both solid-liquid interactions and surface pinning strength contribute to the energy barriers hindering the three-phase contact line motion. For relatively low nanodefect densities, the activation free energy of wetting can be expressed as a sum of surface wettability and surface topography contributions, thus providing a direct link between contact line dynamics and roughness parameters.